Pengungkapan Modal Intelektual - Haryani Chandra (Jurnal Akuntansi, 2021)
All businesses are required to be able to adapt when there is a shift from labor-based business to knowledge-based business. The business shift is also changing the information needed by company’s stakeholders. The stakeholders need adequate information about intellectual capital. Purposes of this study is to provide insight about reasons those support intellectual capital disclosure, obstacles in intellectual capital disclosure, and ways and guidelines in intellectual capital disclosure. This research is a library research. The type of data is secondary data those were obtained from various literatures. The conclusions of this study are intellectual capital have to be disclosed because the information is relevant for decision making made by both internal and external parties; the obstacles in disclose intellectual capital are there are no tool to identify, measure and disclose intellectual capital so companies choose not to disclose intellectual capital continuouisly; and intellectual capital can be disclosed in separate statement which is financial statement supplement while guideline regarding intellectual capital disclosure in Indonesia is stated implicitly in PSAK 19. Keywords: Intellectual Capital, Disclosure